Report on the exchange visits learnings in the six SmartCulTour Living Labs - Mandić, Ante; Petrić, Lidija; Vrgoč, Monika; Kerst, Iris; Koens, Ko; Ferdinandus, Joël; Lioce, Raffaella; Bettin, Michel; Shomali, Kalid W.; Maltauro, Manuela; Alhonsuo, Mira; Björn, Ella; et al. (Zenodo, 2022)
The present Deliverable 6.3 - “Report on the exchange visits learnings in the six SmartCulTour Living Labs” focuses on the hosting and travelling exchange experiences that have been undertaken among the six SmartCulTour Living Laboratories between May and October 2022. The main objective of such activities was to strengthen international cooperation between researchers, advisors and local stakeholders participating in the network of the Labs, develop opportunities for further international cooperation and learning, and support the transfer of knowledge on practical initiatives that could positively influence sustainable cultural tourism development at destination level. In order to boost the relevance of the learning experience, the Living Labs were divided into two groups, based on their typological and geographical coverage: the Split, Rotterdam and Vicenza Living Labs were gathered in an “urban cluster”, while the Utsjoki, Scheldeland and Huesca Living Lab were combined in a “rural cluster”. The exchange reports herein presented are divided per cluster and according to the chronological order of the visits. From a content-wise perspective, the exchange programmes of the Labs within the same cluster - urban or rural - have been designed with a view to maximising overall coherence and complementarity between the different strands of the activity. This report aims at presenting the objectives and results of the exchange programme hosted by each Living Lab, in light of its linkages with the experiences offered by the other two Labs of the same group, as well as the key persons met and potential opportunities for future development and cooperation. Overall, the exchange visit learnings were considered successful from both hosting and travelling Living Labs’ participants, as they proved to be helpful for LLs to test pilot and prototype interventions, exchange good practices on common challenges, and further delve into the potential for cultural tourism development linked to territorial resources, by also relying ...